Factors Supporting Learning Achievement: The Influence of Students' Disciplinary and Motivational Factors of Learning - Suratimah Suratimah; Azam Syukur Rahmatullah; Muhammad Naim Madjid (International Journal of Social Service and Research, 2022)
This study aims to determine the level of the effect of discipline and student learning motivation on student achievement. This research was a hypothesis testing study model with quantitative approach. The data were collected using a questionnaire in Likert scale on discipline and learning motivation, while the data on learning achievement was obtained from school’s documentation. The population was taken from all students of SMK Muhammadiyah 2 Playen Gunungkidul Yogyakarta with a simple random sampling technique having 153 students as the samples. The data analysis consisted of validity and instrument reliability tests, normality tests, linearity tests, hypothesis tests, and correlation tests. The results of this study indicate that 1) learning discipline has a significant effect on student achievement by 12.5% ??and has a moderate correlation with Pearson Correlation score of 0.354; 2) learning motivation has an effect on student achievement by 55.2% and is perfectly correlated with Pearson Correlation score of 0.743; 3) discipline and learning motivation simultaneously have an effect on student achievement of 63.1% with a significance value of 0.000. Meanwhile, 4) the driving factors of discipline are learning readiness, environment, rules, and regulations in the school environment and in teaching and learning activities both at school and at home. On the other hand, the factors that support learning motivation include intrinsic and extrinsic motivation.